PENGARUH INFORMASI KEBANGKRUTAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTARDI BURSA EFEK INDONESIA - Mayrina Ramdhani Nurhayati, - (2009)
When economy crisis happens in Indonesia, most of industrial sectors, including food and beverages experience decline productivity and product actualization. The aims of the study are to find out financial work rate in food and beverages companies listed in Bursa Efek Indonesia in 2003-2007 periods using Z-Score analysis and to find out if the result affects the stock return of the companies. The study is included into descriftive verification research. Sampling technique used in this study is fixed sample method taken from 15 food and beverages companies. The data used is pooled data, meaning it uses secondary data. From the result of the study, it can be concluded that based on Z-Score analysis, most of food and beverages companies at 2003-2006 periods are bankrupt. The data analysis utilities correlation coefficient, determination coefficient and regression analysis. With α = 0.5, the result shows that bankruptcy information has positive influences toward stock return for 14,89% while the rest, 85,11% is influenced by other factors such as rate of interest, foreign exchange broker, Indeks Harga Saham Gabungan (IHSG), etc.